Fall Prevention: Staying Active - Sergio Romero; Linda Bobroff; Wendy Lynch (EDIS)
This publication discusses exercises that can help readers maintain or improve balance, strength, and flexibility. Written by Sergio Romero, Linda B. Bobroff, and Wendy W. Lynch, and published by the UF/IFAS Department of Family, Youth and Community Sciences, revised April 2023.